Fortifications and Organizations of the City of Constantine during the French Colonial Period - MOSBAH, Zoubir; SAHNOUNE , Tayeb (Journal of Human Sciences, 2022)
Colonial ideology was aimed at the emancipation of peoples considered as inferior. By imposing this ideology, socio-spatial metamorphoses would generate cultural, economic and mainly security breaches. These metamorphoses will accomplish the objectives of this ideology, but they will definitely mark the acculturation of a people, for whom the new spatial and socio-cultural data will forever deform its place of identity. The settlement of military troops and migrants from Europe into an existing fabric, juxtaposed established by military engineers in a relatively insidious manner, for the establishment of societies from different countries of the European population. The role of the army is based on the layout of the city wall, its fortifications and military openings, in order to build security equipment (forts and barracks). It is located in the center of communications to easily direct the military troops to the side where their presence will be necessary, reinforce them, or offer them shelter if necessary to reconstitute themselves. The army is thus designated as the prime contractor for all defensive work necessary for colonization for mixed and military territories. The place of Constantine should be protected from the enemy by various methods of fortifications in a protected enclave.